LANGUAGE OF PERSUASION IN ONLINE MARKETING OF COSMETIC PRODUCTS: A GLANCE OF NETNOGRAPHY IN PRAGMATICS - Lina Septianasari; Yasmika Baihaqi; Fourus Huznatul Abqoriyyah; Wuri Syaputri (Universitas Sebelas Maret, 2021)
Online marketing was extensively chosen as the most efficient option to shop during Covid-19 pandemic. Due to the prompt expansion of the digital era, a seller should be creative in using language to persuade buyers. This research aimed to investigate the use of speech acts and persuasion by cosmetics marketers in social commerce to persuade online shoppers. This descriptive research used netnography with pragmatics approach to answering the research questions. Data were collected from Facebook and Instagram by using manual netnography techniques which then scraped into excel as the corpus. After that, the data were analyzed by using the taxonomy of speech acts and persuasion categories. The results show that the use of directive speech acts dominates the persuasion in online marketing of cosmetic products. However, the various type of speech acts and persuasion were used by the online cosmetic sellers as a strategy to promote their products.